Visualisasi Organ Tubuh Dampak Merokok Menggunakan Augmented Reality - Fanindia Purnamasari; Ade Sarah Huzaifa; Dhaffa Safira Ayura (Sekawan Institut, 2025)
Cigarettes are an addictive substance that can cause addiction for those who consume them. Each cigarette contains more than 4,000 types of harmful chemicals for the body. However, smoking has become a habit for some people, especially men, it can harm health and become a source of disease. One of these diseases is coronary heart disease and lung cancer, which are among the leading causes of death due to smoking annually. In 2019, Indonesia had the highest number of teenage smokers in ASEAN, therefore the importance of education about the dangers of smoking is highlight. Public service announcements are a common form of education about the dangers of smoking. According to data, 51.10% of the Indonesian population are active smokers, the highest rate in ASEAN. Raising awareness about the health hazards of smoking, especially to the heart and lungs is crucial and should be conveyed to the public through educational, informative, and interactive media. One such method is the use of multimedia with augmented reality technology. Augmented reality is a technology that can project a 3Dimensional (3D) object into the real world in real-time. This research implements augmented reality using a markerless approach that can display 3D objects of human organs, such as the lungs and heart, affected by smoking.